Reengineering the bank : a blueprint for survival and success - Allen, Paul H. (Chicago, Ill. : Probus Pub. Co., 1994)
Reengineering the Bank helps bankers evaluate their market, operations and, most important, their customers. This guide also discusses the balance sheet, strategies to maximize value, and provides the tools to restructure the program. Now is the perfect time to act: record spreads and profits in the industry can help to fund a forward-thinking restructuring effort. Competition is increasingly fierce, smart and too close to home to ignore. Author Paul Allen, the chairman and founder of Aston Limited Partners, has been involved in bank reengineering processes long before the term itself was coined. His client banks achieve outstanding levels for efficiency and profitability-and enjoy increased shareholder value.
Includes bibliographical references and index.
lje 21/07/16
Loan
Keywords: Banks and banking; Bank management; Organizational change; Reengineering (Management).